Analysis of Risk Factors of ISPA on Improving Mothers' Ability to Self-Care of ISPA in Toddlers at Simalingkar Health Center - Dwi Ris Hasanah; Ristika Julianty Singarimbun (Benih : Journal of Midwifery, 2025)
In Indonesia, Acute Respiratory Infection (ARI) is one of the causes of 4 million deaths in children under five. ISPA is also often on the list of the 10 most common diseases at the Simalingkar Health Center. The mortality rate of ISPA in Indonesia is still very high and morbidity because ISPA in Indonesia per year ranges from 10%-20% of the population under five. Acute Respiratory Tract Infection (ISPA) is an inflammatory process caused by viruses, bacteria, atypical (microplasma), aspiration of foreign substances involving one or all parts of the respiratory tract, a condition in which disease germs successfully attack the body tools used to breathe, namely through the nose, hair, esophagus, throat, throat to the lungs and lasts no more than 14 days. The etiology of ISPA consists of more than 300 types of bacteria, viruses and riketsia. The bacteria that cause ISPA include the genus Streptococci, Staphylococci, Pneumococcus, Haemofillus, Bordetelia and Corinebacterium. The viruses that cause ISPA include Myxoviruses, Adnoviruses, Coronaviruses, Pikornaviruses, Mycoplasma, Herpesviruses and others. In addition to being caused by viruses and bacteria, ISPA is also caused by microplasma or aspiration of foreign substances involving one or all parts of the respiratory tract. Studies in various countries show that in developing countries Streptococus pneumonia and Haemofillus influenza are bacteria that are always found in two-thirds of the isolation results, namely 73.9% of lung aspirates and 69.1% of the isolation results from blood specimens. Meanwhile, in developed countries, adult pneumonia in children is generally caused by a virus. ISPA can be transmitted through saliva, sneezing, and breathing air that contains germs that are inhaled by healthy people into their respiratory tract. ISPA that continues to become pneumonia often occurs in children, especially if there is malnutrition and combined with unhygienic environmental conditions. Germs of ISPA disease are transmitted from the patient to others through the air of breathing or the spitting of the sufferer. In principle, the ISPA germs in the air are sucked in by the new host and enter the entire respiratory tract. From the respiratory tract, germs spread throughout the body if the infected person is vulnerable, then he will be affected by ISPA.